Alcune teorie della monetizzazione a confronto - Gianpaolo Rossini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1985)
– Is money going to be replaced by an information processor simila/ to the Walrasian auctioneer? At the heart of the question theae is the role of money in transactions. Niehans (1971) stated that money emerges as the good with the lowest transaction cost out of a barter economy and its appearance can also turn non—traded goods into traded—goods. Jones (1976) and Schoetter (1981) emphasize the institutional role of money whose diffusion parallels the provision of a public good.Freeman (1985) underlies the market completeness of money and its role in transa—ctions vis a vis other assets.Gale (1978;1983) says that markets cannot be Debreu—complete without outside money. The roles of money in Niehans,Jones,Schoetter can be superseded.The one in Freeman—Gale cannot,since money has a role even if information is perfect and free because it makes markets complete.A contract will never be equivalent to a money payment.
Keywords: 330